Synaptic activation in guinea-pig dentate area: dependence on the stimulation site - Brunner, Hans; Misgeld, Ulrich (Pflügers Archiv, 1993)
A negative-going and a positive-going field potential were evoked in the granule cell layer by electrical stimulation of a region near the cell layer (commissural/associational fibres, cf) and of the lateral perforant path (perforant-path fibres, pp). The cf-evoked field potential was more strongly reduced by (-)baclofen (2-5 μmol l−1) and carbachol (2-5 μmol l−1) than was the pp-evoked field potential. By simultaneous intra and extracellular recordings, the elements activated from the two stimulation sites were determined. Stimulation of cf-fibres elicited concurrently excitatory and inhibitory postsynaptic potentials, but inhibition predominated, pp stimulation elicited excitation followed by inhibition, and excitation predominated. Responses evoked from both stimulation sites were affected by antagonists for glutamatergic excitation. Inhibition blockade revealed that excitation elicited from the cf-stimulation site was largely shunted by inhibition. Presumed inhibitory neurons in the dentate hilus were driven at latencies consistent with the latencies at which inhibition was elicited in granule cells from the two stimulation sites. We conclude that the sequence of synaptic events produced by extracellular stimulation can vary substantially by slightly differing electrode placements. However, it is difficult to decide, simply on the basis of an extracellular field potential, what elements have been activated.
Gesehen am 08.04.2021